Cyclic AMP Regulates Bacterial Persistence through Repression of the Oxidative Stress Response and SOS-Dependent DNA Repair in Uropathogenic Escherichia coli - Roberto C. Molina-Quiroz (American Society for Microbiology, 2018)
ABSTRACT Bacterial persistence is a transient, nonheritable physiological state that provides tolerance to bactericidal antibiotics. The stringent response, toxin-antitoxin modules, and stochastic processes, among other mechanisms, play roles in this phenomenon. How persistence is regulated is relatively ill defined. Here we show that cyclic AMP, a global regulator of carbon catabolism and other core processes, is a negative regulator of bacterial persistence in uropathogenic Escherichia coli, as measured by survival after exposure to a β-lactam antibiotic. This phenotype is regulated by a set of genes leading to an oxidative stress response and SOS-dependent DNA repair. Thus, persister cells tolerant to cell wall-acting antibiotics must cope with oxidative stress and DNA damage and these processes are regulated by cyclic AMP in uropathogenic E. coli. IMPORTANCE Bacterial persister cells are important in relapsing infections in patients treated with antibiotics and also in the emergence of antibiotic resistance. Our results show that in uropathogenic E. coli, the second messenger cyclic AMP negatively regulates persister cell formation, since in its absence much more persister cells form that are tolerant to β-lactams antibiotics. We reveal the mechanism to be decreased levels of reactive oxygen species, specifically hydroxyl radicals, and SOS-dependent DNA repair. Our findings suggest that the oxidative stress response and DNA repair are relevant pathways to target in the design of persister-specific antibiotic compounds.